Cover Feature: Spectroelectrochemical Sensor for Spectroscopically Hard‐to‐detect Metals by in situ Formation of a Luminescent Complex Using Ru(II) as a Model Compound (Electroanalysis 11/2018). Issue 11 (15th November 2018) - Lines, Amanda M.; Warner, Joshua D.; Heineman, William R.; Clark, Sue B.; Bryan, Samuel A.
Abstract : Spectroelectrochemical Sensor for Spectroscopically Hard‐To‐Detect Metals by In‐Situ Formation of a Luminescent Complex Using Ru(II) as a Model Compound This image shows the general method of electrogeneration of an emissive, electrochemically reversible ruthenium complex, with the concurrent spectroscopic measurement. More details are discussed in the article by Amanda M. Lines, Joshua D. Warner, William R. Heineman, Sue B. Clark, and Samuel A. Bryan. DOI:10.1002/elan.201800427